2010
DOI: 10.1007/s10802-010-9413-2
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the Tripartite Dimensions of Affect for Anxiety and Depression in Youth: Examining Sex and Psychopathology Status

Abstract: Using a combined sample (N=1,215) of referred children and children from the general population aged between 8 and 14 years, the present study addressed two research goals: First, latent mean differences (depending on the individual's sex or psychopathology level) in anxiety, depression, Positive Affect (PA), Negative Affect (NA) and Physiological Hyperarousal (PH) were examined. Secondly, the structure of anxiety and depression was investigated from a tripartite model perspective in boys and girls with high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…In addition, some research indicates that as emotions become more specific and outcome dependent with development, children's increasingly sophisticated attributions result in previously undifferentiated feelings states (e.g., anxiety or depression; Weiner & Graham, 1988). Based on this theory, De Bolle, Decuyper, De Clercq, and De Fruyt (2010) suggest that younger children who experience problems of depression or anxiety are likely to report a general malaise. Later in development, specific symptoms may be attributed to specific environmental entities or may be interpreted as signs of imminent danger, which may result in specific fears or phobias and generalized anxiety, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some research indicates that as emotions become more specific and outcome dependent with development, children's increasingly sophisticated attributions result in previously undifferentiated feelings states (e.g., anxiety or depression; Weiner & Graham, 1988). Based on this theory, De Bolle, Decuyper, De Clercq, and De Fruyt (2010) suggest that younger children who experience problems of depression or anxiety are likely to report a general malaise. Later in development, specific symptoms may be attributed to specific environmental entities or may be interpreted as signs of imminent danger, which may result in specific fears or phobias and generalized anxiety, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is reason to expect that an FAB-anxiety relation will exist. For example, remember that dysphoria has already been explored in FAB research, and empirical evidence documents a robust association between depressive symptoms and anxiety ( De Bolle, Decuyper, De Clercq, & De Fruyt, 2010 ; Fajkowska, 2013 ; Judah et al, 2013 ). Third, anxiety is seen by some as reflecting an emotion-regulation deficit associated with excessive worry (see Behar, DiMarco, Hekler, Mohlman, & Staples, 2009 ; Orgeta, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their samples did not allow for the explicit test of clinical status or sex as a moderator. Nevertheless, research has indicated meaningful mean level differences between boys and girls and between community and referred children with respect to anxiety, depression, and the tripartite dimensions [19][20][21][22][23][24][25][26][27]. Therefore, it would be interesting to investigate whether and to what extent these mean-level sex and referred status differences affect the associations between anxiety and depression on the one hand and the tripartite dimensions on the other.…”
Section: Introductionmentioning
confidence: 99%